2020
DOI: 10.1055/s-0040-1712541
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal Duodenal Diverticulum: A Rare Cause of Chronic Epigastric Pain

Abstract: AbstractDespite its first identification in 1885, intraluminal duodenal diverticulum remains a rare entity and only a few case reports are found in the literature. Its diagnosis is almost always delayed due to the lack of specific symptoms and to the very vague presentation consisting of mild epigastric discomfort. However, with the aid of new diagnostic modalities and imaging, it has become easier to diagnose this entity when its symptoms persist. Finally, it can remain undiag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For example, levels of amylase and bilirubin may be normal until there is an obstruction in the biliary or pancreatic duct. Because of the long-term stimulation of the diverticulum content and a lack of innervation and peristaltic waves, an IDDD can significantly enlarge and develop a huge lumen ( 19 ). The only symptom experienced by our present case was recurrent abdominal pain because of the enormous cavity, mild compression, and communication with the tract, with no obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, levels of amylase and bilirubin may be normal until there is an obstruction in the biliary or pancreatic duct. Because of the long-term stimulation of the diverticulum content and a lack of innervation and peristaltic waves, an IDDD can significantly enlarge and develop a huge lumen ( 19 ). The only symptom experienced by our present case was recurrent abdominal pain because of the enormous cavity, mild compression, and communication with the tract, with no obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Due to gastric and duodenal obstruction in our patient, she was recommended surgical diverticulectomy, however, conservative management was requested per patient. Historically, surgical intervention was performed for gastric and bowel obstruction [1,12]. Nowadays, with advancements in endoscopy and imaging; endoscopic diverticulotomy or diverticulectomy is the treatment of choice.…”
Section: Obstructionmentioning
confidence: 99%
“…Nowadays, with advancements in endoscopy and imaging; endoscopic diverticulotomy or diverticulectomy is the treatment of choice. The endoscopy approach includes using needle-knife papillotomy, sphincterotomy, argon plasma coagulation, yttrium aluminum garnet (YAG) laser, and endostapler have been described [7][8][9][10][11][12][13][14][15][16][17]. In a study by Bhalla et al, the use of a novel technique reported as submucosal dissection scissors (SB knife, (Olympus, Shinjuku City, Tokyo, Japan)) and blended the longitudinal wall by electrocautery showed resolution of symptoms [14].…”
Section: Obstructionmentioning
confidence: 99%